2009
DOI: 10.1007/s10637-009-9324-7
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic efficacy of sorafenib and genistein in growth inhibition by down regulating angiogenic and survival factors and increasing apoptosis through upregulation of p53 and p21 in malignant neuroblastoma cells having N-Myc amplification or non-amplification

Abstract: Neuroblastoma is an extracranial, solid, and heterogeneous malignancy in children. The conventional therapeutic modalities are mostly ineffective and thus new therapeutic strategies for malignant neuroblastoma are urgently warranted. We examined the synergistic efficacy of combination of sorafenib (SF) and genistein (GST) in human malignant neuroblastoma SK-N-DZ (N-Myc amplified) and SH-SY5Y (N-Myc non-amplified) cell lines. MTT assay showed dose-dependent decrease in cell viability and the combination therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 42 publications
(67 reference statements)
1
22
0
Order By: Relevance
“…The combination of nutritional factors with anti-cancer drugs has been suggested to be a potential strategy for cancer therapy [17][18][19]33]. In this study, we report for the first time that BI had the potential to enhance the metastasis-inhibitory effect of SF in SK-Hep-1 cells.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The combination of nutritional factors with anti-cancer drugs has been suggested to be a potential strategy for cancer therapy [17][18][19]33]. In this study, we report for the first time that BI had the potential to enhance the metastasis-inhibitory effect of SF in SK-Hep-1 cells.…”
Section: Discussionmentioning
confidence: 73%
“…Several studies have suggested that nutritional factors may cooperatively or synergistically enhance the effect of anti-cancer drugs to inhibit the metastasis of cancer cells through various mechanisms [17][18][19]. For example, Roy Choudhury et al [19] found that combination of SF and genistein synergistically inhibited angiogenic and survival factors and increased apoptosis in both neuroblastoma SK-N-DZ and SH-SY5Y cell lines. Furthermore, combination therapy may reduce the toxicity of chemotherapy [20].…”
Section: Introductionmentioning
confidence: 99%
“…Cells were re-suspended in PBS, fixed with 70% ethanol, labeled with staining solution (0.05 mg/ml PI, 2 mg/ml RNase A, 0.1% TritonX-100 in PBS), and incubated for 30 min at room temperature (RT) in darkness. DNA content was then analyzed using an Epics XL-MCL Flow Cytometer (Beckman Coulter, Fullerton, CA), as we reported recently [21].…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…Cells were washed with cold PBS, resuspended in 19 binding buffer (0.1 M HEPES/NaOH, pH 7.4, 1.4 M NaCl, 25 mM CaCl 2 ), stained with Annexin V-FITC/PI, and incubated for 15 min at RT in the darkness. Cells were analyzed for Annexin V-stained apoptotic population using an Epics XL-MCL Flow Cytometer (Beckman Coulter, Fullerton, CA), as per our previous reports [20,21].…”
Section: Flow Cytometric Analysis Of Apoptosismentioning
confidence: 99%
See 1 more Smart Citation